Search for leptonic charge asymmetry in tt¯W $$ t\overline{t}W $$ production in final states with three leptons at s $$ \sqrt{s} $$ = 13 TeV. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Top Physics.; Springer Open.